Presidential discourse on public policy: The cases of health and education during the Concertación governments (1990-2009) - López, Miguel Ángel; Vilchez, Ulises; Miranda, Nicolás (Estado, Gobierno y Gestión Pública, 2011)
<span style="font-size: 12.0pt; font-family: ";Cambria";,";serif";; mso-ascii-theme-font: major-latin; mso-hansi-theme-font: major-latin; mso-bidi-font-family: AGaramondPro-Regular; mso-ansi-language: EN-US;" lang="EN-US">This article uses Baumgartner and Jones’ policy agenda theoretical and methodological framework to study the Concertación presidents’ May 21 (state of the union) speeches, with an aim towards determining the importance, as well as changes and continuities, that health and education are given in the public policy agenda.